2017
DOI: 10.1007/s11419-017-0361-1
|View full text |Cite|
|
Sign up to set email alerts
|

In vitro and in vivo pharmacokinetics and metabolism of synthetic cannabinoids CUMYL-PICA and 5F-CUMYL-PICA

Abstract: CUMYL-PICA [1-pentyl-N-(2-phenylpropan-2-yl)-1H-indole-3-carboxamide] and 5F-CUMYL-PICA [1-(5-fluoropentyl)-N-(2-phenylpropan-2-yl)-1H-indole-3-carboxamide] are recently identified recreationally used/abused synthetic cannabinoids, but have uncharacterized pharmacokinetic profiles and metabolic processes. This study characterized clearance and metabolism of these compounds by human and rat liver microsomes and hepatocytes, and then compared these parameters with in vivo rat plasma and urine sampling. It also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
70
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 35 publications
6
70
2
Order By: Relevance
“…Similar dehalogenation and further oxidation reactions have been reported as major metabolic pathways for 5F‐AMB, THJ‐2201, 5F‐AB‐PINACA, AM‐2201, XLR‐11, 5F‐PB‐22, 5F‐CUMYL‐PICA, 5F‐AKB‐48, and 5F‐MDMB‐PICA …”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Similar dehalogenation and further oxidation reactions have been reported as major metabolic pathways for 5F‐AMB, THJ‐2201, 5F‐AB‐PINACA, AM‐2201, XLR‐11, 5F‐PB‐22, 5F‐CUMYL‐PICA, 5F‐AKB‐48, and 5F‐MDMB‐PICA …”
Section: Resultssupporting
confidence: 77%
“…All the metabolites identified using HLMs were observed in authentic human urine samples, except for M14. Similarly, for CUMYL‐PICA, 5F‐CUMYL‐PICA, and NNEI N ‐dealkylation metabolite was reported in vitro, but not detected in urine samples . We also detected 5F‐ADB as the parent drug in 12 of the 30 authentic urine samples.…”
Section: Resultssupporting
confidence: 64%
“…However, similarities in diagnostic ions were observed. Two common fragments, m/z 144 and m/z 232, observed in PX‐1 and similar PICA SCs are characteristic of the indole core and fluoropentyl tail . The fragments m/z 145, 233, and 213 were observed in the elucidation of PX‐2 and other PINACA compounds and are characteristic of the indazole core and fluoropentyl tail .…”
Section: Resultsmentioning
confidence: 82%
“…Phase I metabolism studies revealed that CUMYL‐PEGACLONE is an extensively metabolized SC. In contrast to former cumyl‐derivatives, the main in vivo metabolite M20 was unexpectedly hydroxylated at the γ ‐carbolinone core whereas former analogs were mainly hydroxylated at the pentyl side chain . The metabolites M20 and M09 were identified as sensitive and specific urinary markers to proof uptake of this highly prevalent substance.…”
Section: Discussionmentioning
confidence: 99%